Study of Principles for Compiling Country-Specific Chinese Teaching Materials for Indonesia - Kelly Rosalin (Bina Nusantara University, 2013)
This article analyzes an Indonesian version of Contemporary Chinese teaching material. It is found that in this teaching material there are several problems relating to the content of text, translation, and context of text if it is used by Indonesian students. Therefore, it needs to consider “five elements” of language, cultural, and teaching principles in compiling the Chinese teaching materials for Indonesian students.